Evaluation of Satisfaction Levels of Women Journalists With Regards to the Consumption of OTT Contents: A Study of Karnataka - Philomina; Kolar, Tahmeena Nigar Sultana (UIR Press, 2024)
In our everyday lifestyle we spend too much time in front of electronic gadgets. The vast range of development of media and visual entertainment is not a big thing for everyone and it’s widely accessible through mobile phones. The new form of media content spreading through the streaming services means OTT Platforms like Amazon Prime Video, Netflix, Voot, Zee5, and etc. availability of OTT Platforms is not a big thing because many streaming platforms give such a freemium option for their viewers. But one thing we all should be aware of is that some contents are released on OTT because they are unlikely to be released on theatre and TV, which is subject to regulation by the Central board of film certification (CBFC) and Broadcasting content complaints council (BCCC) and etc. So, Streaming Platforms has not any regulatory restriction to broadcast web contents and it gets more liberty in the absence of censorship. The main purpose of this study to assess awareness of OTT platforms among women journalists and to know satisfaction level of OTT Content. For this study descriptive research method was adopted and the primary data collected through the survey method. A total 80 number of the respondents were selected. It is found from the study that majority of the women journalist were aware about the OTT platform and they were very satisfied with the content of the OTT.